El comportamiento y actitudes del consumidor hacia la comercialización de productos Agroecológicos en la Ciudad de Riobamba. - Jaramillo Quinzo, Nataly Sthefania (2022)
The organic agriculture development has been promoted as the need to improve family´s food safety, this kind of agriculture is not the exception in Ecuador. The research was carried out in order to know the influence of the costumer´s behavior and attitude to the agro-ecological products commercialization in Riobamba which will help to understand what situations is the consumer involved to access to this product, the producer´s position on the market. On the other hand, if there is preference to this product or there is not preference to consume them; a descriptive study, deductive method and non-experimental design were used. The techniques used to get the data were the survey and the interview which allow to know the demographic and cultural factors, these are the most important ones to determine the consumer´s behavior to the agro-ecological products commercialization in Riobamba. The psychological factors determined the consumers` attitude to the agro-ecological products commercialization in Riobamba.